Tratamento de manipueira vizando a minimização de impactos no ambiente concomitante ao cultivo de microalgas para obtenção de bioenergia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
In recent decades, several scientific studies have focused on the production of microalgae and their potential, both for effluent treatment and energy production. The interest in the massive cultivation of microalgae directly influenced the optimization of photobioreactors treating wastewater rich in nutrients, in addition to the generation of byproducts. Industrial effluents come from the intense use of water in industries, among the sectors that produce the most wastewater is the agro-industrial starch sector. In Pará, the flour mills stand out where the cassava derivatives generated are to supply the industrial sectors of: food, medicine, mining, cosmetics, alcoholic beverages, and others. The effluent that comes from this sector is called manipueira. In order to reduce the environmental impacts caused by industrial effluent from flour mills (cassava) and analyze the feasibility of generating byproducts from microalgal biomass, the objective of this study aimed to promote the bioremediation of these industrial wastewaters by optimizing the photobioreactor called Immobilized Microalgae Reactor (RMI) to obtain better productivity in the formation of algal biomass and treated effluents. The RMI operated on a laboratory scale with optimized hydraulic detention time, analyzing its performance regarding the physical-chemical parameters of the system's input and output concomitant with the cultivation of microalgae to verify its potential in biomass production. The RMI operated with a useful volume of 1200mL and as energy for photosynthetic activity, two LED lamps were used for a period of 24 hours to keep the reactor's photosynthetic process active, and two dosing pumps were used to control the flow and recirculation of the system, respectively. As for the physical-chemical results in the final effluent, they reached more than 90% of nitrogen (NH4+) and phosphorus (PO43-) and organic material (in the form of COD). In this sense, it was also possible to obtain a gradual quantity of algal biomass and identify the genera of microalgae through optical microscopy and the use of taxonomic keys, a very relevant data for the quality and production of bioenergy.
Keywords: Tratamento Biológico; Sustentabilidade; Pós-tratamento de efluentes; Agroindustria; Biomassa; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS